PENGARUH PEMBERIAN BAHAN ORGANIK TERHADAP SIFAT KIMIA PADA TANAH SAWAH TERDEGRADASI DI KECAMATAN PANTAI LABU KABUPATEN DELI SERDANG - Salman Alfarisi; Deni Elfiati; Abdul Rauf (Talenta Publisher, 2017)
Organic fertilizers provide an advantage in increasing the growth and yield and can reduce the use of inorganic fertilizers. The study aims to analyze the land rehabilitation efforts relegated to improve the properties of the fields of chemistry, physics, and biology of the soil, with compare paddy soil conditions before and after rehabilitation. thereby increasing the productivity of rice in the District of Pantai Labu. The research was conducted in Durian, District, Pantai Labu, Deli Serdang, North Sumatra in April 2017 to July 2017. The study was arranged in a randomized block design (RAK) non-factorial experiment with five treatments and four replications. The treatments used are B0 = Control, B1 = 1.5%, B2 = 3%, B3 = 4.5%, B4 = 6%. The results showed that organic fertilizer can increase plant growth indicated by an increase in plant height. Organic fertilizers also increase the number of productive tillers, panicle length. Organic fertilizers also increase the number of grains per panicle and filled the grain.